Why Would Presbyterians Turn to a Catholic Document? - Moses, Jay; Ficca, Dirk; Sawyer, Nanette; Cathey, Robert; Folan, Jill; Rains, Katie (Studies in Christian-Jewish Relations, 2016)
No abstract is available.